Reflexiones sobre la dirección escénica y la praxis teatral - Geirola, Gustavo (Universidad de Costa Rica, 2015)
This article reports on the artistic perspective of 115 Latin American theatrical direc- tors on issues related to the mise-en-scène; interviews took place in 19 countries all over the three Americas. Grouped into 6 volumes published under the title Art and Craft of the Theater Director in Latin America, interviews cover multiple aspects involved in the process of producing a show (reading of the dramatic text, rehearsals, performan- ce, promotion, etc.). They establish a corpus of knowledge on theatrical praxis; such knowledge constitutes a database of enormous wealth because it not only opens a new debate on professional issues but also gives a broad overview of the director’s work in different socio-cultural contexts.